Wheels of change: Transforming girls' lives with bicycles - Nathan Fiala; Ana Garcia-Hernandez; Kritika Narula; Nishith Prakash (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
Reducing the gender gap in education is a primary goal for many countries. Two major challenges for many girls are the distance to school and their safety when commuting to school. In Zambia, we studied the impact of providing a bicycle to a school-going girl who lives more than 3 km from the school. We randomized whether a girl received a bicycle with a small cost to her family to cover replacement parts, a bicycle where these costs are covered by the program, and therefore is zero cost to the family, or a control group. One year after the intervention, we find that the bicycle reduced average commuting time to school by 35%, reduced late arrival by 66%, and decreased absenteeism by 27%. We find continued improvement in girls' attendance and reduction in dropouts two, three, and four years after the intervention. We also find evidence of improved math test scores, girls expressing higher feelings of control over their lives and, for those who received bicycles with a small cost to her family, higher levels of aspirations, self-image, and a desire to delay marriage and pregnancy. Heterogeneity analysis by distance to school shows an inverted U-shape for most of the schooling and empowerment results, suggesting greater impact for girls that live further away from school. These results suggest that empowerment outcomes worked through increased attendance in school. – – Die Verringerung von geschlechtsspezifischen Bildungsunterschieden ist für viele Länder ein vorrangiges Ziel. Für zahlreiche Mädchen sind die Entfernung zur Schule und ihre Sicherheit auf dem Schulweg zwei große Herausforderungen. In Sambia untersuchten wir den Effekt der Bereitstellung eines Fahrrads für Mädchen, die zur Schule gehen und mehr als 3 km von der Schule entfernt wohnen. Wir unterschieden nach dem Zufallsprinzip, ob ein Mädchen ein Fahrrad erhielt, bei dem die Familie geringe Kosten für Ersatzteile tragen musste, ein Fahrrad, bei dem alle Kosten durch das Programm abgedeckt wurden, oder ob es Teil der Kontrollgruppe war. Ein Jahr nach der Maßnahme stellten wir fest, dass ein Fahrrad die durchschnittliche Schulwegzeit um 35% verkürzt, Zuspätkommen um 66 % reduziert und Fehlzeiten um 27% verringert hat. Auch zwei, drei und vier Jahre nach der Maßnahme hat sich die Anwesenheit der Mädchen zunehmend verbessert und die Anzahl der Schulabbrecherinnen verringert. Außerdem finden wir Belege für bessere Ergebnisse in Mathematiktests, für das Gefühl der Mädchen, mehr Kontrolle über ihr Leben zu haben, und unter denjenigen, die Fahrräder zu geringen Kosten für ihre Familie erhalten haben, für höhere Ambitionen, ein besseres Selbstbild und den Wunsch, Heirat und Schwangerschaft aufzuschieben. Eine Heterogenitätsanalyse nach Schulentfernung zeigt eine umgekehrte U-Form für die meisten Ergebnisse zu Schulbildung und Empowerment, was auf eine größere Wirkung der Maßnahme für Mädchen hindeutet, die weiter von der Schule entfernt wohnen. Diese Ergebnisse deuten darauf hin, dass Empowerment durch höheren Schulbesuch erzielt wurde.
Keywords: H42; I21; I25; J16; O15; 330; Girls' education; attendance; dropout; grade transition; test scores; bicycles; female aspiration; female empowerment; safety; Zambia